2015
DOI: 10.1007/s40121-015-0076-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Dynamic Model for Health Economic Analysis of Influenza Vaccination in the Elderly

Abstract: IntroductionNew vaccines are being developed to improve the efficacy of seasonal influenza immunization in elderly persons aged ≥65 years. These products require clinical and economic evaluation to aid policy decisions.MethodsTo address this need, a two-part model has been developed, which we have applied to examine the potential clinical and economic impact of vaccinating elderly persons with adjuvanted trivalent inactivated influenza vaccine (aTIV) relative to conventional trivalent (TIV) and quadrivalent (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Of these 35 studies, 2 studies were excluded after screening titles and abstracts, and from 18 studies no full-text was available as these referred to conference abstracts only. As one additional study that met our inclusion criteria was identified outside the initial search, we ended up with 16 eligible studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The flowchart of the study identification process is displayed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these 35 studies, 2 studies were excluded after screening titles and abstracts, and from 18 studies no full-text was available as these referred to conference abstracts only. As one additional study that met our inclusion criteria was identified outside the initial search, we ended up with 16 eligible studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The flowchart of the study identification process is displayed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…One study comprised a main paper and a corrigendum [27,36]. Of these 16 studies, 2 did not primarily focus on the cost-effectiveness of QIV as compared with TIV, but on high-dose TIV [21] or adjuvanted TIV [29] as compared with TIV and QIV. However, as both studies reported detailed results of TIV and QIV, we included these studies in our review.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations